2020
DOI: 10.1186/s12889-020-08549-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of front-of-pack nutrition labels on consumer purchasing intentions: a randomized experiment in low- and middle-income Mexican adults

Abstract: Background: Front-of-pack (FOP) nutrition labeling is a cost-effective strategy to help consumers make informed and healthier food choices. We aimed to investigate the effect of the FOP labels used in the Latin American region on consumers' shopping intentions when prompted to make their choices with specific nutrients-to-limit in mind among low-and middle-income Mexican adults (> 18 y). Methods: In this experimental study of an online simulated shopping situation participants (n = 2194) were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 48 publications
(57 reference statements)
3
53
0
2
Order By: Relevance
“…However, previous studies of individuals have found that those with higher incomes are more likely to see and use calorie menu labels than those with lower incomes [34][35][36]. Based on prior studies, other labeling systems (e.g., traffic light labels and warning labels) may be more effective than nutrient disclosures [37,38], particularly among low-and middle-income populations [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies of individuals have found that those with higher incomes are more likely to see and use calorie menu labels than those with lower incomes [34][35][36]. Based on prior studies, other labeling systems (e.g., traffic light labels and warning labels) may be more effective than nutrient disclosures [37,38], particularly among low-and middle-income populations [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food retailers may be reluctant to test interventions they view as potentially harmful to sales, such as taxes or warning labels. Another viable option is to conduct experiments in virtual 3D stores [38][39][40], which may facilitate faster and more affordable recruitment, although the simulated shopping environment is not as realistic as a physical store. Finally, some studies have used experimental online stores intended to replicate online grocery shopping or food ordering websites [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…While the healthier fruit drink contained 18% of the daily value of sugar, the less healthy fruit drink contained 44% of the daily value of sugar; a difference of 26 percentage points. In a real life shopping situation, the ability to closely compare GDA labels on different products might be more limited as people have less time to examine the labels in detail [31]. In addition, the nutrient warning label performed better than the GDA on the majority of other outcomes, including: helping consumers to correctly identify products as having excess of sugar, saturated fat, or sodium; discouraging purchasing the product in the next week if it were available; and increasing perceived message effectiveness.…”
Section: Discussionmentioning
confidence: 99%